The legend of Zelda. Twilight princess, Volume 10 - Himekawa, Akira; Stan!, 1964- (The legend of Zelda, 2022)
Sensing that total victory and the complete destruction of Hyrule are within his grasp, Ganondorf unleashes his armies. Link, Midna, their friends, and many others they have met on their journey now fight side by side to save the land. Even a former enemy ends up allied with Link as he presses on into the heart of Ganondorf's stronghold. When Link confronts Ganondorf, defeating him will take every ounce of skill and courage he has....